IMPLEMENTASI AWIG-AWIG PERKAWINAN TERHADAP KETAHANAN SOSIAL KEAGAMAAN DI DESA ADAT TENGANAN PEGRINGSINGAN - I Nengah Juliawan; Putu Ersa Rahayu Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Bali is one of the provinces in Indonesia, with customary law regulated in awig-awig which has become an agreement in the customs that apply in indigenous people which are shown to regulate the needs of the community, one of which is the marriage rule. Traditional marriages held in the Tenganan Pegringsingan traditional village are an inner and outer bond between men and women carried out with a series of sacred events in order to form and build a safe and controlled family based on awig-awig which incidentally is the basis of social resilience of the Tenganan Pegringsingan traditional village communitywhich has been regulated in Article 4, Article 5, Article 15, Article 16, Article 32, Article 40, Article 49, Article 50, Article 56, and Article 57. This manuscript is based on qualitative research, through descriptive analysis methods and ethnographic approaches.Keywords: awig-awig, marriage, social resilience